PENGELOLAAN FLIGHT INFORMATION REGION WILAYAH UDARA INDONESIA DALAM KASUS ETHIOPIAN AIRLINES ETH 3728 BERDASARKAN KONVENSI CHICAGO 1944: Indonesian Airspace Flight Information Region Management in the Case of Ethiopian Airlines ETH 3728 Based on the Chicago Convention 1944 - Rifdah Izni; Sugeng Supartono (Faculty of Law, Universitas Trisakti, 2026)
The management of Indonesia's Flight Information Region delegated to Singapore raises sovereignty challenges, particularly in the case of the Ethiopian Airlines ETH 3728 violation in 2019, which entered the airspace of the Riau Islands without direct permission from Indonesia. The research problem is whether Indonesia's delegation of FIR management to Singapore complies with the 1995 bilateral agreement and the 1994 Chicago Convention, and whether Indonesia has the authority to enforce the law against foreign aircraft entering its airspace without permission where the FIR is managed by Singapore. The research method employed is normative legal research that is descriptive, using secondary data in the form of primary and secondary legal materials analyzed qualitatively. The research findings indicate that discrepancies between practices and the agreement's content, along with inadequate coordination between Singaporean and Indonesian aviation authorities, led to this airspace violation by Ethiopian Airlines. Indonesia also holds the authority to enforce the law through force down actions based on Article 1 of the 1944 Chicago Convention and Law Number 1 of 2009 on Aviation. In conclusion, Indonesia's airspace sovereignty remains exclusive, and strengthened coordination as well as updates to the bilateral agreement are needed to prevent future sovereignty violations.